EFL students' self-efficacy in technology-assisted language learning - Istikharoh, Lutfi; Utami, Sri Yuli (Universitas Islam Negeri Banda Aceh, 2024)
Technological advancements are currently available in several areas to meet our daily needs. One such development is the use of technology in education, which has seen a significant increase in recent times due to the Covid-19 epidemic. Although students may be familiar with blended learning and technology, it is important for teachers to assess their level of self-efficacy in using technology effectively in education, as this has a direct impact on their ability to learn and improve their academic performance. This study investigated the level of students' self-efficacy and explored strategies to enhance it among Indonesian students who are now enrolled in an English Language Education program after the outbreak. This survey research integrated both quantitative and qualitative data analysis methods. Data was collected through interviews and questionnaires. A total of 60 students participated in this research. The questionnaire resulted in an overall self-efficacy score of 76.6% for all participants. This percentage indicates the high level of self-efficacy of the students. Each year group is classified as high. Interviews with the students served to validate the questionnaire results and further supported these findings. The majority of students use three ways to improve their English as a Foreign Language (EFL) acquisition. They participate autonomously in English language practice by improving computer skills, using online educational media and resources, and intensifying engagement with teachers and peers through communication platforms.